Assessment of the impact of vehicle emissions on the geoecological state of soils and vegetation in the cities of the Irkutsk agglomeration - Svetlana A. Novikova (RUDN Journal of Ecology and Life Safety, 2023)
The study examines the problem of the influence of vehicle emissions on the condition of soils and vegetation of roadside strips in the cities of the Irkutsk agglomeration. Sampling was carried out near intersections characterized by intense traffic flows. As a result of a mass (semi-quantitative) full spectral analysis of selected samples, the content of heavy metals in them was revealed to be higher than the maximum permissible and background concentrations. Calculations of the total pollution indicator were carried out, which made it possible to establish that the soils of roadside zones in urbanized areas of the agglomeration belong to the categories “dangerous” and “extremely dangerous”. Recommendations for improving the geoecological condition of soils and vegetation in urban areas are given.